2021
DOI: 10.3390/ijerph18115948
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising Risk Factors for Prescription Drug Overdose among Older Adults in South Korea: A Multi-Method Study

Abstract: Older adults are vulnerable to drug overdose. We used a multi-method approach to prioritise risk factors for prescription drug overdose among older adults. The study was conducted in two stages. First, risk factors for drug overdose were classified according to importance and changeability through literature review, determined through 2-phase expert surveys. Second, prescription drug overdose cases during 2011–2015 were selected from a national cohort; the prevalence of ‘more important’ or ‘more changeable’ fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Death from drug overdose has been steadily increasing and remains a major public health problem. 1 , 2 , 22 Therefore, many previous studies focused on the risk of suffering an overdose 7 , 8 , 23 , 24 or the epidemiological aspects of overdose a social viewpoint. 1 , 2 , 5 , 22 Around 70% of drug overdose deaths in the United States are related to opioids 25 ; however, opioid overdose is very rare in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death from drug overdose has been steadily increasing and remains a major public health problem. 1 , 2 , 22 Therefore, many previous studies focused on the risk of suffering an overdose 7 , 8 , 23 , 24 or the epidemiological aspects of overdose a social viewpoint. 1 , 2 , 5 , 22 Around 70% of drug overdose deaths in the United States are related to opioids 25 ; however, opioid overdose is very rare in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…As drug overdose is an important social issue, there have been many studies on the prevalence and mortality of drug overdose, 1 , 5 , 6 and some of these studies focused on the risk factors for a drug overdose. 7 , 8 Other previous studies demonstrated the risk factors for complications or death caused by drug overdose, and most of them reported on the specific type of drugs involved, such as paracetamol 9 or opioids, 10 which are common and highly toxic in large doses. Regarding grading the severity of drug overdoses, some studies, including the poisoning severity score developed by the International Programme on Chemical Safety and the Swedish Poisons Information Service, suggested that the clinical parameters and symptoms available in the ED could be used to predict which patients would require treatment in medium care units or intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, research efforts have studied the prevalence, etiological factors, and estimated outcomes of nurses' prescription drug misuse [15]. However, in South Korea, although prescription drug misuse has been investigated in limited studies (e.g., in older persons [20]), there is a lack of research on nurses' prescription drug misuse. Overseas research may not be generalizable to the Korean context because drug use in South Korea and North America, in general, are quite different; drug use in Asian countries is regarded as a crime rather than a public health problem [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a five-year longitudinal study by Chang et al (2020) observed over 2 million (67%) polypharmacy-related hospitalizations among the sample of older adults studied [9]. Polypharmacy also increases the risk of accidental and intentional drug poisoning [1,10]. While medications are a mainstay of medical treatment for older adults with chronic conditions, when someone goes home from the hospital, clinic, and pharmacy, they are largely left to develop their own routine and system for medication management and organization.…”
Section: Introductionmentioning
confidence: 99%